The paths followed in the training of a group of teacher researchers - Albarracin de Carvajal, Alba Socorro (Rastros Rostros, 2023)
I present to the academic community and other readers who will enjoy reading the magazine "Rastros y Rostros" the path taken by a group of Early Childhood Education students with emphasis in Spanish Language to carry out their research practice.